Annual Report on Exchange Arrangements and Exchange Restrictions 1974. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1974)
This paper discusses that with inflows of capital showing some further expansion, the combined overall balance of payments surplus of the developing countries remained high. Most of the countries that use the French franc, pound sterling, or the US dollar as their intervention currency continue to do so with no change in the relationship between their own currency and the intervention currency involved. However, some countries like Jamaica re-pegged from sterling to the US dollar. Despite the flexible exchange rate regime operating in relation to the major currencies, measures to curb capital inflows, particularly those on short-term funds taken in 1971 and strengthened thereafter, were not relaxed in general until after mid-1973. The first relaxation came after a strengthening of the US dollar against the major European currencies in the third quarter of the year. During the period under review the Bahamas became a member of the IMF, raising total membership to 126 countries.